A newsreel history of the Third Reich. Volume 10, Bombing of Paris [videorecording (DVD)]. (Artsmagic, 2007)
Follow the second part of the year 1942, covering events on all the German fronts including the home front as Hitler attends Day of Commemoration in Berlin; Western Front-the RAF bombing of Paris; and more.